Eastern Caribbean Currency Union : Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
The objective of this paper is to analyze the growth performance of the ECCU countries since independence and the policy challenges they face to ensure sustained growth in the period ahead. Although tourism specialization may bring about higher growth, it could also increase volatility in growth by amplifying the impact of business cycles in source countries on the tourism sector. Low productivity growth is principally the reason for the slowdown in growth. High debt levels have been a major drag on growth.